Morfosintaksis Konstruksi Verba Bahasa Jawa: Kajian Tipologi - Herpindo, Herpindo; Wulandari, Sri; Ariefian, Maftukhin; Shohibul Ghoni, Ahmad; Aulia Rahman, Fandi (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2025)
This research is motivated by the structural form of the Javanese language, particularly its agglutinative morphology, which has the potential to exhibit morphosyntactically dynamic behavior, especially in verb constructions that serve as the core of a constituent. The method used in this research is a descriptive qualitative approach to examine the phenomenon as it exists in Javanese grammatical construction (Morphosyntactic Verb Construction). Exemplary and Distributional methods are used to analyse the data. The findings in this study show that verb construction in Javanese has the following pattern dynamics; (i) transitive active verb construction with morphological marker prefix meN with allomorphs m-, n-, ng-, and ny- and passive patterns into di-, di-i, kok-, and tak-; (ii) intransitive verb constructions with zero Ø morphemes; (iii) anti-passive ergative constructions with ke- and ke-an morphemes; and (iv) ergative with zero Ø constructions. The findings in this study also show that the dynamics of verb construction in Javanese are not limited to one type of grammatical behavior (typology); moreover, ergative typology appears to be a new tendency.